Use of medication in competition horses. Issue 7 (14th July 2016) - Termine, Caterina
Abstract : The Fédération Equestre Internationale (FEI) is the world governing body of equestrian sport. Horses participating in FEI events are subject to Equine Anti‐Doping and Controlled Medication testing for the presence of Prohibited Substances. The role of the veterinarian is essential in evaluating a horse's fitness to compete, selecting appropriate medication when a horse requires treatment close to and during competition, and providing relevant advice to prevent positive test results. If a veterinarian's actions constitute a violation of the FEI regulations, sanctions can be imposed upon them as well as on the athlete. This article describes the role of the FEI and veterinarians at such equestrian events and gives details of the procedures that need to be undertaken if a horse needs treatment close to or during competition.